THE INFLUENCE OF REVISIT INTENTION AND SELF-CONCEPT ON E-WOM BASED ON THEORY OF PLANNED BEHAVIOR - Albana, Deasa Nurrhausan; Marsasi, Endy Gunanto (Jurnal Ekonomi Bisnis dan Kewirausahaan, 2023)
This study aims to investigate the influence of revisit intention and self-concept on electronic word-of-mouth (E-WOM) among Gen Z using the Theory of Planned Behavior, particularly Mixue Ice Cream Tea consumers. In this quantitative study, the data was collected using a questionnaire distributed to 250 respondents, and was analyzed using Structural Equation Modeling (SEM). The results show that self-concept positively influences the revisit intention. Revisit intention is positively and significantly influenced by perceived price justice and satisfaction. Perceived price justice is identified as influencing loyalty positively and significantly, while perceived satisfaction influences loyalty positively and significantly. Revisit intention affects loyalty showing a positive and significant relationship, while E-WOM is identified to be positively and significantly influenced by loyalty. The implications of this research are relevant for food and beverage companies to strategize their business strategy to increase consumer confidence so that it will affect E-WOM.JEL: M31, M21, L84.